Politique et machine judiciaire : entre concubinage notoire et recherche d’efficacité dans l’action prétorienne (African Journal of Law and Politics, 2023)
The intrusion of political agencies into the judiciary directly challenges the duty of objectivity and loyalty of magistrates. Consequently, the consolidation of the independence of justice becomes more and more in Cameroon as everywhere else, the only pledge of a development justice. If the anxiety of underdevelopment also comes from the weaknesses of the judicial authorities, it is however necessary to note that hope remains, because justice opened up or under orders, it would be necessary that one day, that one turns resolutely towards a more just justice, freed from all individual passion, from all political pressure and all social heaviness linked to favoritism or concussion.